2005
DOI: 10.1063/1.1901806
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast double-pulse ablation of fused silica

Abstract: Ultrafast pump-probe experiments were used to study high-intensity ultrafast pulse-ablation dynamics in fused silica. Two laser pulses with varied time delay and pulse energy were used to irradiate fused silica samples and observe the transient reflectivity and transmissivity of the probe pulse. It was seen that the probe reflectivity initially increased due to the formation of free-electron plasma and then dropped to a low value within a period of about 10ps caused by a rapid structural change at the surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…For pulses below the damage threshold the material typically shows very little plasma emission and no optical modification that can be investigated. Using double-or multipulse trains, it has been shown that a noncritical electron plasma can be produced well below the permanent damage threshold [18,19,28]. Results from simulations that access those regimes are very important to the study of this interaction and should be confirmed by experiment.…”
Section: Introductionmentioning
confidence: 96%
“…For pulses below the damage threshold the material typically shows very little plasma emission and no optical modification that can be investigated. Using double-or multipulse trains, it has been shown that a noncritical electron plasma can be produced well below the permanent damage threshold [18,19,28]. Results from simulations that access those regimes are very important to the study of this interaction and should be confirmed by experiment.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, we have used double pulses with separations of up to 3.4 ns in a pump probe experiment to study a transition region between two logarithmic fluence regimes. Fairly extensive experimental results have been reported on ''single pulse'' femtosecond metal ablation, though few specifically on silver [3,7] but results on dual (or multiple) pulse ablation have been rather more limited [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. By dual pulse it is always understood that the pulse separation is much less than the interpulse period (typically 1 ms) of the train of amplified femtosecond pulses used for ablation.…”
Section: Introductionmentioning
confidence: 99%
“…These can range from electron lattice relaxation times or electron diffusion times (a few ps to a few 100 ps) to times for the development of the ablation plume (up to a few 1000 ps) [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…dielectrics follow short-and long-living absorption phases, associated to carrier dynamics in strong or weak interaction with the glass matrix [7,[13][14][15] . The material structurally responds to this dynamics on various timescales with structural states ranging from densification (type I) to rarefaction (type II) [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%